2021
DOI: 10.3389/fimmu.2021.666543
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses to Wildtype and Attenuated Sheeppox Virus Mediated Through RIG-1 Sensing in PBMC In-Vitro

Abstract: Sheeppox (SPP) is a highly contagious disease of small ruminants caused by sheeppox virus (SPPV) and predominantly occurs in Asia and Africa with significant economic losses. SPPV is genetically and immunologically closely related to goatpox virus (GTPV) and lumpy skin disease virus (LSDV), which infect goats and cattle respectively. SPPV live attenuated vaccines (LAVs) are used for vaccination against SPP and goatpox (GTP). Mechanisms related to innate immunity elicited by SPPV are unknown. Although adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…5A-C). Additionally, retinoic acid inducible gene 1 (Rig-1) has been con rmed to mediate impaired cell death and immune responses [35][36][37]. Our results showed that compared to the sham group, the AAC group showed a signi cant reduction in RIG-1 expression.…”
Section: Resultsmentioning
confidence: 75%
“…5A-C). Additionally, retinoic acid inducible gene 1 (Rig-1) has been con rmed to mediate impaired cell death and immune responses [35][36][37]. Our results showed that compared to the sham group, the AAC group showed a signi cant reduction in RIG-1 expression.…”
Section: Resultsmentioning
confidence: 75%
“…However, whether either of these viruses completed their replication cycle in PBMCs to produce infectious progeny was not shown (Chibssa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%